2022
DOI: 10.3390/ijms23116030
|View full text |Cite
|
Sign up to set email alerts
|

Critical Review on Fatty Acid-Based Food and Nutraceuticals as Supporting Therapy in Cancer

Abstract: Fatty acids have an important place in both biological and nutritional contexts and, from a clinical point of view, they have known consequences for diseases’ onset and development, including cancer. The use of fatty acid-based food and nutraceuticals to support cancer therapy is a multidisciplinary subject, involving molecular and clinical research. Knowledge regarding polyunsaturated fatty acids essentiality/oxidizability and the role of lipogenesis-desaturase pathways for cell growth, as well as oxidative r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 157 publications
0
7
0
Order By: Relevance
“…FA supplements are naturally involved in membrane formation, lipid remodeling, and membrane-based signaling processes that occur in vivo and have the same potential to affect biological function as endogenously produced molecules (87). Lipidomic analysis showed that fatty acid composition of membrane and cellular lipid pool is continuously remodeled by the influence of free fatty acid availability, including endogenous synthesis and exogenous uptake (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…FA supplements are naturally involved in membrane formation, lipid remodeling, and membrane-based signaling processes that occur in vivo and have the same potential to affect biological function as endogenously produced molecules (87). Lipidomic analysis showed that fatty acid composition of membrane and cellular lipid pool is continuously remodeled by the influence of free fatty acid availability, including endogenous synthesis and exogenous uptake (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…However, the promising results of ketogenic diets in animal studies and early clinical case series have been difficult to demonstrate in recent systematic reviews and meta-analyses of human trials. Sufficiently powered, randomized controlled trials are required to prove the benefits [ 216 , 217 , 218 , 219 , 220 ] ( Figure 11 ).…”
Section: Weight Loss and Prevention Of Cancermentioning
confidence: 99%
“…However, the promising results of ketogenic diets in animal studies and early clinical case series have been difficult to demonstrate in recent systematic reviews and meta-analyses of human trials. Sufficiently powered, randomized controlled trials are required to prove the benefits [216][217][218][219][220] (Figure 11). Obesity and metabolic syndrome not only increase the risk of primary cancers, but also influence prognosis after cancer treatment [221][222][223][224][225].…”
Section: Weight Loss and Prevention Of Cancermentioning
confidence: 99%
“…Today's people are more knowledgeable and interested in health-related issues than ever before. Today, many journals in the field of medicine give wide coverage to research in this field (9)(10)(11).…”
Section: Nutraceuticalsmentioning
confidence: 99%